A Long‐Term View of Episodic Tremor and Slip in Cascadia - Noel M. Bartlow (Geophysical Research Letters)
Abstract Episodic Tremor and Slip, or ETS, is a well‐recognized phenomenon in the Cascadia subduction zone. Constraining the precise location of geodetically measured slip during ETS is important for clarifying the relationship between slip and tremor during ETS, the location of ETS slip relative to the strongly locked zone, and the role of ETS in the overall slip budget. Here I present a new method for separating Global Navigation Satellite System time series in Cascadia into ETS and inter‐ETS components, deriving long‐term average ETS velocities for each site. These velocities are then inverted for a time‐averaged ETS slip rate on the plate interface. I find that ETS and its role in the slip budget are highly variable and segmented along strike. This inversion represents the highest‐resolution image of the ETS zone derived from geodetic data to date. Slip correlates well with tremor locations, and a possible second updip ETS zone is detected.